THE APPROACHES TO FORMATION OF SYSTEM OF ECOLOGICAL INDICATORS AS THE PART OF THE SYSTEM OF INDICATORS OF POWER SECURITY - Bikova E.V.; Tsaranu M.Y.; Kirillova T.I. (Problems of the Regional Energetics)
The statement of the task of necessity of more detailed study of questions of ecological security for RМ is executed as the part of energy security in light of consideration of a question of association of the markets of the electric power «East - West" in the article. The system of indicators of ecological security is generated. It includes indicators accepted as uniform for all countries Eurelectric EU-CIS, and also additional indicators, and has interrelations with system of indicators used for the analysis of energy security RМ. The structure of the possible analysis of ecological security is given, the initial data are prepared and the accounts for the part of ecological indicators are carried out.